Frontiers in Vascular Stiffness (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The evaluation of vascular stiffness is becoming increasingly important in cardiovascular research to determine the properties of the arterial tree and clinically assesspatients. Current research addresses and debates some unresolved technical and methodological issues with measuring arterial stiffness, with the purpose of making it more reliable and clinically suitable. This Special Issue focuses on new methodological advances in vascular stiffness, as well as preclinical and clinical applications. A privileged space is reserved for new data and targeted reviews of the application of arterial stiffness and early vascular ageing measures regarding problems such as the stratification of risk of special populations and specific diseases.